Amazing makerspace DIY electricity - Holzweiss, Kristina (New York, NY : Children's Press, an imprint of Scholastic Inc., 2018)
Learn how to complete DIY [do it yourself] projects dealing with electricity. Along the way, get a look at some of history's most incredible inventions and scientific discoveries.
You can be a maker! -- Light-up birthday card -- Steady hand game -- The big truth!: Thomas Edison's bright ideas -- Homemade flashlight -- Famous inventors and pioneers -- Timeline.
Includes bibliographical references (page 45) and index.
5.6
3-6
770L
STEAM
Keywords: Electricity -- Experiments -- Juvenile literature; Electricity -- Experiments; Science -- Experiments; Makerspaces -- Juvenile literature; Handicraft